Supramolecular Assembly-Induced Emission Enhancement for Efficient Mercury(II) Detection and Removal - Dai, Dihua; Li, Zheng; Yang, Jie; Wang, Chunyu; Wu, Jia-Rui; Wang, Yan; Zhang, Dongmei; Yang, Ying-Wei (Journal of the American Chemical Society, 2019)
New strategies that can simultaneously detect and remove highly toxic environmental pollutants such as heavy metal ions are still in urgent need. Herein, through supramolecular host–guest interactions, a fluorescent supramolecular polymer has been facilely constructed from a newly designed [2]biphenyl-extended pillar[6]arene equipped with two thymine sites as arms (H) and a tetraphenylethylene (TPE)-bridged bis(quaternary ammonium) guest (G) with aggregation-induced emission (AIE) property. Interestingly, supramolecular assembly-induced emission enhancement (SAIEE) could be switched on upon addition of Hg2+ into the above-mentioned supramolecular polymer system to generate spherical-like supramolecular nanoparticles, due to the restriction of intramolecular rotation (RIR)-related AIE feature of G. Significantly, this supramolecular polymer with integrated modalities has been successfully used for real-time detection and removal of toxic heavy metal Hg2+ ions from water with quick response, high selectivity, and rapid adsorption rates, which could be efficiently regenerated and recycled without any loss via a simple treatment with Na2S. The newly developed supramolecular polymer system combines the inherent rigid and spacious cavity of novel extended-pillarene host with the AIE characteristics of TPE-based guest, suggesting a great potential in the treatment of heavy metal pollution and environmental sustainability.